Predictors of enrollment in opioid agonist therapy after opioid overdose or diagnosis with opioid use disorder: A cohort study. (1st February 2021) - Macmadu, Alexandria; Paull, Kimberly; Youssef, Rouba; Batthala, Sivakumar; Wilson, Kevin H.; Samuels, Elizabeth A.; Yedinak, Jesse L.; Marshall, Brandon D.L.
Highlights: The majority (58 %) did not enroll in opioid agonist therapy within 6 months. Prior overdose, alcohol use disorder, and back problems predicted non-enrollment. ED and PCP visits above the 75th percentile were associated with timely enrollment. We identified high-impact healthcare settings to enhance pathways to treatment. Abstract: Background: Medicaid recipients have a high burden of opioid overdose and opioid use disorder (OUD). Opioid agonist therapies are an effective treatment for OUD, but there is a wide and persisting gap between those who are indicated and those who receive treatment. The objective of this study was to identify the predictors of enrollment in opioid agonist therapy within 6 months of an opioid overdose or OUD diagnosis in a cohort of Medicaid recipients. Methods: Using multiple linked, state-level databases, we conducted a retrospective cohort study of 17, 449 Medicaid recipients in Rhode Island who had an opioid overdose or an OUD diagnosis between July 2013 and June 2018. Results: The majority (58 %) of Medicaid recipients did not enroll in opioid agonist therapy within 6 months. In adjusted models, having one or more prior overdose (adjusted risk ratio [ARR] = 0.33, 95 % CI: 0.28, 0.38), alcohol use disorder (ARR = 0.56, 95 % CI: 0.52, 0.60), or back problems (ARR = 0.58, 95 % CI: 0.55, 0.61) were strong predictors of non-enrollment. Conversely, emergency department (ARR = 1.31, 95 % CI: 1.28–1.34) and primary care provider (ARR = 1.03, 95 % CI: 1.01–1.34) visit frequency above the 75th percentile were associated with timely enrollment in opioid agonist therapy. Conclusions: Our findings underscore the need to enhance pathways to treatment for OUD through varied nodes of engagement with healthcare systems. Interventions to improve screening for OUD and referrals to opioid agonist therapies should include high-impact settings, such as treatment programs for alcohol and substance use disorders, pain clinics, and outpatient behavioral care settings.